"Amidah" - Trods Redningsmænd og ofre i oktober 1943 - Lene Bak, Sofie (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
The article identifies trends and potentials in the historiography of the rescue of the Danish Jews in October 1943. The perception of the rescue had been extraordinarily consensual until the 1990s when studies revealed that persecution had strategically low priority in Denmark. This conclusion changed the fixed roles of both persecutors and rescuers into a more nuanced perception that allowed for German pragmatism and Danish abuse. In collective memory, by contrast, stereotypes hardened in a post-war society where patriotic martyrs were more instrumental than victims of a meaningless racial ideology. Focus was almost exclusively on the rescuers, with little room for mourning the dead and lost. In recent years, collective memory in Denmark has been internationalized with a growing attention to the victims, but it signifies a risk of an Americanization of memory that dissolves ambiguity and universalizes the event. The gulf between historiography and memory can be bridged by a renewed research interest in the victims, for example by applying the concept of Amidah to the Danish case. Amidah, translated from Hebrew into “Defiance”, embraces any act of opposition to the Nazis in the process of dehumanization that ultimately culminated in death. By this definition, any act that saved lives can be regarded as resistance. Through examples of Jewish rescuers, recently uncovered cases of Hidden Children in Denmark and Jewish experiences of exile and return, the article demonstrates the potential of further exploring the perspective of the victims, not only turning passive objects of persecution into active subjects but also placing the events in October 1943 firmly in a larger context of the European Holocaust.